Involvement of Cholesterol Membrane Transporter Niemann-Pick C1-Like 1 in the Intestinal Absorption of Lutein - Yuki Sato; Risa Suzuki; Masaki Kobayashi; Shirou Itagaki; Takeshi Hirano; Toshihiro Noda; Satoshi Mizuno; Mitsuru Sugawara; Ken Iseki (Frontiers Media S.A., 2012)
PURPOSE. Lutein is a carotenoid mainly found in green leafy vegetables and is located in the macula lutea in the human eye. Since humans cannot synthesize lutein de novo, it must be digested as food. The physiological importance of an orally administered compound depends on its interaction with target tissues. It is therefore important to clarify the absorption mechanism in the intestine. Cholesterol membrane transporters Niemann-Pick C1 Like 1 (NPC1L1) and scavenger receptor class B type 1 (SR-B1) are involved in the intestinal absorption of highly lipophilic compounds including cholesterol. Ezetimibe, a selective inhibitor of intestinal NPC1L1, is the widespread lipid-lowering agent. It is important to investigate the possibility of food-drug interactions in order to prevent undesirable and harmful clinical consequences. The aim of this work was to determine whether NPC1L1, SR-B1 and other transporters are involved in absorption of lutein. METHODS. Caco-2 cells were used for accumulation and permeability study of lutein. Lutein concentration was determined by an HPLC system. The cDNA of transporters was isolated from total RNA of Caco-2 cells, and the expression of these transporters was confirmed by RT-PCR (reverse transcription - polymerase chain reaction). RESULTS. Ezetimibe inhibited up to 40% of lutein accumulation by Caco-2 cell monolayers. Block lipid transport 1 (BLT-1), a selective chemical inhibitor of SR-B1, also inhibited lutein accumulation by Caco-2 cells. On the other hand, ATP-depletion reagents (sodium fluoride and sodium azide or carbonyl cyanide m-chlorophenylhydrazone) did not influence the accumulation or permeation of lutein significantly. CONCLUSIONS. The results show that lutein absorption is, at least in part, mediated by influx transporters NPC1L1 and SR-B1 rather than mediated by efflux transporters such as ABC (ATP-binding cassette) transporters. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.